Global Smile: Navigating The World of Dental Tourism - Dr. Deeksha Kaundal; Dr. Sakshi Agarwal; Dr. Saim Khan; Dr.Mohnish Muchhal (Revista Electronica de Veterinaria, 2024)
Dental tourism, also referred to as dental holidays, is an aspect of medical tourism that includes people who, while on vacation, seek dental care outside of their native healthcare systems. Due to its outstanding and reasonably priced dental services, India has also become a popular destination for dental tourists as dental tourism grows globally. However, there are people still have to overcome numerous obstacles in order to benefit from this industry. The government plays a crucial role in eliminating the complications of the procedure; for instance, it can streamline the medical visa application process and implement visa-on-arrival for patients to increase the promotion of dental services to tourists.